The correlation of age and extension length in DeBakey type I aortic dissection: are older patients over 70 years at a lower risk? - Merkle-Storms, Julia; Gaisendrees, Christopher; Feißt, Manuel; Rylski, Bartosz; Dohle, Daniel-Sebastian; Hagl, Christian Matthias; Lescan, Mario; Brickwede, Jens; Poeling, Jochen; Holubec, Tomas; Etz, Christian D.; Jawny, Philipp; et al. (European journal of cardio-thoracic surgery, 2023)
Age-related atherosclerosis has been shown to cause aortic stiffness and wall rigidification. This analysis aimed to correlate age and dissection extension length in a large contemporary multicentre study. We hypothesize that younger patients suffer more extensive DeBakey type I dissection due to aortic wall integrity, allowing unhindered extension within the layers.The perioperative data of 3385 patients from the German Registry for Acute Aortic Dissection Type A were retrospectively analyzed with regard to postoperative outcomes and dissection extension. Patients with DeBakey type I aortic dissection (n = 2510) were retrospectively identified and divided into 2 age groups for comparison: ≤69 years (n = 1741) and ≥70 years (n = 769). Patients with DeBakey type II dissection or connective tissue disease were excluded from the analysis.In younger patients (≤69 years), aortic dissection involved the supra-aortic vessels significantly more often (52.0% vs 40.1%; P < 0.001) and extended significantly further downstream the aorta: descending aorta (68.4% vs 57.1%; P < 0.001), abdominal aorta (54.6% vs 42.1%; P < 0.001) and iliac bifurcation (36.6% vs 26.0%; P < 0.001). Consequently, younger patients also presented with significantly higher incidences of preoperative cerebral (P < 0.001), spinal (P < 0.001), visceral (P < 0.001), renal (P = 0.013) and peripheral (P < 0.001) malperfusion. In older patients (≥70 years), dissection extent was significantly more often limited to the level of the aortic arch (40.9% vs 29.2%; P < 0.001). No significant difference was found with regard to 30-day mortality (20.7% vs 23.6%; P = 0.114).Extensive DeBakey type I aortic dissection is less frequent in older patients ≥70 years than in younger patients. In contrast, younger patients suffer more often from preoperative organ malperfusion and associated complications. Postoperative mortality remains high irrespective of age groups.